PB101, a VEGF- and PlGF-targeting decoy protein, enhances antitumor immunity and suppresses tumor progression and metastasis - Eun-Jin Go; Hannah Yang; Seung Joon Lee; Hyun Gul Yang; Jin A. Shin; Won Suk Lee; Hye Seong Lim; Hong Jae Chon; Chan Kim (OncoImmunology)
Antiangiogenic therapy is a recognized method for countering the immunosuppressive tumor microenvironment (TME) and improving anti-tumor immunity. PB101 is a glycosylated decoy receptor that binds to VEGF-A and PlGF with high affinity, based on the VEGFR1 backbone. Here, we elucidated PB101-induced remodeling of tumor angiogenesis and immunity, which enhances anti-PD-L1 immune checkpoint blockade. PB101 inhibited tumor growth by suppressing angiogenesis and enhancing CD8+ T cell infiltration into the tumors. PB101 induced robust reprogramming of antitumor immunity and activates intratumoral CD8+ T cells. Anti-tumor efficacy of PB101 is mostly dependent on CD8+ T cells and IFN-γ. PB101 reprograms tumor immunity in a manner distinct from that of the conventional VEGF decoy receptor, VEGF-trap. With its potent immune-modulating capability, PB101 synergizes with an anti-PD-L1, triggering strengthened antitumor immunity. Combining PB101 and anti-PD-L1 could establish durable protective immunity against tumor recurrence and metastasis. The findings of this study offer scientific rationales for further clinical development of PB101, particularly when used in combination with immune checkpoint inhibitors, as a potential treatment for advanced cancers.